TWO NEW SPECIES OF ARGULUS MULLER (CRUSTACEA: BRANCHIURA) FROM RIVER CAUVERY WITH A KEY TO INDIAN SPECIES - Thomas, M M; Devaraj, M (Indian Journal of Fisheries, 2011)
Two new species of Argulus Muller viz., A. fluviatilis and A. cauveriensis collected from River Cquvery at Hoginekal, South India, are described, with a discussion on their affinity to the other Indian species. The paper also provides a key to the Indian species of Argulus